Estado de exceção na obra de Giorgio Agamben: da politização da vida à comunidade que vem - Leutério, Alex Pereira (2014)
This research objectives at the investigation of the state of emergency in the light of the work of Giorgio Agamben, in the sense of an instrument capable of, by law, stop the life and rights inherent to it by its own suspension in empty space of law, a zone of anomie. Thus, Agamben historically reports the zone of indifference from institutes of Roman law that produced the stoppage of the law and therefore a legal loophole. Given this finding, Agamben correlates such institutes to the state of contemporary Exception, which is, in fact, permanent, put that in this vacuum, standard and life are connected by force-in-law, which applies, diapplying. Will point out that Agamben begins his argument by examining the political power and its relation to biological life (zoé), analysis of biopower and the movement of inclusive exclusion of biological life in the field of politics and law. Then, we stress that the political work of Giorgio Agamben records the infamous debate between Carl Schmitt and Walter Benjamin, about the sovereign power, from which it extracts the state of permanent exception and the field are paradigms of contemporary politics - like Auschwitz , "homo sacer" and "Muselmann - legitimized by the founding violence of law, the considerations discussed here is done on biopolitics, bare life, the state of exception and force of law, whose solution, for Agamben, is a new form of life, achieved by the desecration, which reflects a community coming, endowed with the ability to disable biopower mentioned, creator of a-bando-ned, and not necessarily linked to the law. In conclusion, upon the concepts and profanation inoperosidade the proposed Agamben turns out something totally new, since this community requires that comes a new ethos, a new use, a shutdown of the old use, rendering them inoperable, since being any will be neither a people united by their similarities (aryans, africans, indians) or divided groups or subgroups, shredded by differences singularity without identity, common and absolutely exposed, the actual path of contemplation of the evangelicmessage of zoé aiónios, of eternal life